Auto-antibodies to the receptor tyrosine kinase MuSK in patients with myasthenia gravis without acetylcholine receptor antibodies. - Hoch, W; McConville, J; Helms, S; Newsom-Davis, J; Melms, A; Vincent, A (2001)
Myasthenia gravis (MG) is an antibody-mediated autoimmune disease of the neuromuscular junction. In approximately 80% of patients, auto-antibodies to the muscle nicotinic acetylcholine receptor (AChR) are present. These antibodies cause loss of AChR numbers and function, and lead to failure of neuromuscular transmission with muscle weakness. The pathogenic mechanisms acting in the 20% of patients with generalized MG who are seronegative for AChR-antibodies (AChR-Ab) have not been elucidated, but there is evidence that they also have an antibody-mediated disorder, with the antibodies directed towards another, previously unidentified muscle-surface-membrane target. Here we show that 70% of AChR-Ab-seronegative MG patients, but not AChR-Ab-seropositive MG patients, have serum auto-antibodies against the muscle-specific receptor tyrosine kinase, MuSK. MuSK mediates the agrin-induced clustering of AChRs during synapse formation, and is also expressed at the mature neuromuscular junction. The MuSK antibodies were specific for the extracellular domains of MuSK expressed in transfected COS7 cells and strongly inhibited MuSK function in cultured myotubes. Our results indicate the involvement of MuSK antibodies in the pathogenesis of AChR-Ab-seronegative MG, thus defining two immunologically distinct forms of the disease. Measurement of MuSK antibodies will substantially aid diagnosis and clinical management.